Determinants of Bank Profitability of Indonesian Banks Based on Core Capital Size in Category 3 And 4 - Karen Santoso; Weindytha Patrizia Wibowo; Sammy Kristamuljana; Rathria Arrina Rachman (Studi Akuntansi dan Keuangan Indonesia, 2020)
Since December 2012, the Central Bank of Indonesia has been grouping banks into four classes based on the size of core capital requirement, namely Buku 1, Buku 2, Buku 3 and Buku 4. These categories primarily determine the scope of banks’ business activities. This research aimed to identify the determinants of banks’ profitability in the Buku 3, Buku 4, and the combination of Buku 3 and Buku 4 categories. The data sample was 27 conventional commercial banks consisting of 23 banks from Buku 3 and 4 banks from Buku 4 listed on the Indonesia Stock Exchange (BEI) from 2009 to 2018. By applying multiple linear regressions to panel data, the results showed that net interest margin (NIM) positively affected profitability of the banks in Buku 3, Buku 4, as well as Buku 3 and Buku 4 category. Moreover, operating expense to operating income ratio (BOPO) and non-performing loan (NPL) negatively affected profitability of those banks. However, loan to deposit ratio (LDR) and capital adequacy ratio (CAR) was shown to have negative relationships with profitability only for banks in Buku 4. Accordingly, this study finds that banks in different sizes of core capital category have different factors affecting profitability in the Indonesian banking sector.